Replacement Value of Cashew-nut Meal for Soyabean Meal in Finishing Broiler Chickens - Ojewola, G.S.; Okoye, F.C.; Agbakuru, I. (International Journal of Poultry Science, 2004)
In a 5 week feeding trial, cashewnut meal was substituted for Soyabean meal at 0, 25, 50, 75 and 100% and the diets were respectively designated as diets 1, 2, 3, 4 and 5 in a completely randomized design. Body weight changes, feed intake, feed-to-gain ratio and the economics of production were investigated. The feed-to-gain ratio was significantly (p<0.05) influenced while other parameters were not. Diet 3 gave the best value (2.24) followed closely by diets 4 (2.25) and 2 (2.28) respectively, while diet 1 had the poorest value (2.53) followed by diet 5 (2.40). The mean daily feed intake numerically improved as the percent cashewnut meal substitution increased from 0 to 100%. Birds fed diet 4 had the highest value (120.58g) while birds fed diet 1 had the least value (115.84g). The mean total body weight gain (g) was highest (2214g) for birds fed diet 3 while birds fed diet 1 had the least value (1878.00g). The cost/kg diet (N) decreased as the dietary inclusion of the test ingredient increased from 0 to 100%. At the end of the trial, the highest marginal revenue was obtained from birds fed diet 4 (N415.32). This was closely followed by birds fed diets 3, 5, 2 and 1. Cashewnut meal is therefore recommended as a substitute for the expensive conventional plant proteins at 25, 50 and 75% levels.